DYSTOCIA DUE TO CONJOINED SIAMESE TWIN MONSTER IN A BUFFALO: A CASE REPORT - SINGH, A K; BRAR, P S; PANDEY, A K; PRABHAKAR, S; PRABHAKAR, S; GANDOTRA, V K (The Indian Journal of Animal Reproduction, 2010)
A rare case of dystocia due to conjoined siamese twin monster in a buffalo and its successful management is described.